Kościół wobec nowelizacji z 10 lutego 1976 roku Konstytucji PRL (1952) - Mażewski, Lech (Czasopismo Prawno-Historyczne, 2009)
The Church protests against the plans to amend the Polish People's Republic Constitution of 1976 were rather successful, and in consequence the government had partially given up the proposed amendments. In the Church's view, the real problem was not the dominance of the United Polish Workers' Party, but the Soviet influences in Polish People's Republic. It was felt that although, at that particular moment of history, even the authoritarian system and limited independence could be, if reluctantly, accepted, the powers of the government needed to be clearly demarcated and free from ideological obligations, including implementation of official atheism. Those limes were a manifestation of the integrity of human rights and the family, the respect for the Church and its place in public life, and, above all, from the fact that Poland of those time enjoyed a relatively wide internal and external autonomy.